Rhynchophylline Ameliorates Endothelial Dysfunction via Src-PI3K/Akt-eNOS Cascade in the Cultured Intrarenal Arteries of Spontaneous Hypertensive Rats - Hao, Hui-Feng; Liu, Li-Mei; Pan, Chun-Shui; Wang, Chuan-She; Gao, Yuan-Sheng; Fan, Jing-Yu; Han, Jing-Yan (Frontiers in Physiology, 2017)
Objectives: To examine the protective effect of Rhynchophylline (Rhy) on vascular endothelial function in spontaneous hypertensive rats (SHRs) and the underlying mechanism. Methods: Intrarenal arteries of SHRs and Wistar rats were suspended in myograph for force measurement. Expression and phosphorylation of endothelial nitric oxide (NO) synthase (eNOS), Akt and Src kinase (Src) were examined by Western blotting. NO production was assayed by ELISA. Results: Rhy time- and concentration-dependently improved endothelium-dependent relaxation in the renal arteries from SHRs, but had no effect on endothelium-independent relaxation in SHR renal arteries. Wortmannin (an inhibitor of phosphatidylinositol 3-kinase) or PP2 (an inhibitor of Src) inhibited the improvement of relaxation in response to acetylcholine by 12 hour-incubation with 300 µM Rhy. Western blot analysis revealed that Rhy elevated phosphorylations of eNOS, Akt and Src in SHR renal arteries. Moreover, wortmannin reversed the increased phosphorylations of Akt and eNOS induced by Rhy, but did not affect the phosphorylation of Src. Furthermore, the enhanced phosphorylations of eNOS, Akt and Src were blunted by PP2. Importantly, Rhy increased NO production and this effect was blocked by inhibition of Src or PI3K/Akt. Conclusion: The present study provides evidences for the first time that Rhy ameliorates endothelial dysfunction in SHRs through the activation of Src-PI3K/Akt-eNOS signaling pathway.